Design of Vertically Aligned Binocular Omnistereo Vision Sensor. (26th August 2010) - Tang Tang, Yi-ping Yi-ping; Wang Wang, Qing Qing; Zong Zong, Ming-li Ming-li; Jiang Jiang, Jun Jun; Zhu Zhu, Yi-hua Yi-hua
Abstract : Catadioptric omnidirectional vision sensor (ODVS) with a fixed single view point is a fast and reliable single panoramic visual information acquisition equipment. This paper presents a new type of binocular stereo ODVS which composes of two ODVS with the same parameters. The single view point of each ODVS is fixed on the same axis with face-to-face, back-to-back, and faceto- back configuration; the single view point design is implemented by catadioptric technology such as the hyperboloid, constant angular resolution, and constant vertical resolution. The catadioptric mirror design uses the method of increasing the resolution of the view field and the scope of the image in the vertical direction. The binocular stereo ODVS arranged in vertical is designed spherical, cylindrical surfaces and rectangular plane coordinate system for 3D calculations. Using the collinearity of two view points, the binocular stereo ODVS is able to easily align the azimuth, while the camera calibration, feature points match, and other cumbersome steps have been simplified. The experiment results show that the proposed design of binocular stereo ODVS can solve the epipolar constraint problems effectively, match three-dimensional image feature points rapidly, and reduce the complexity of three-dimensional measurement considerably.